Incidence of Pulmonary Disease Caused by Mycobacteria other than Tuberculosis in British Columbia - R Kevin Elwood; Anabelle M Opazo Saez; Vittorio Lentini; Ramak Shadmani (Canadian Respiratory Journal)
CONTEXT: The incidence of pulmonary disease due to mycobacteria other than tuberculosis (TB) in Canada has not been documented.